Implementasi Akad Musyarakah Pada Pertanian Sistem Mertelu (Studi Kasus: Kelompok Tani Sido Makmur Desa Sabrang Ambulu) - Pratiwi, Izzatul Juhan Salsa Bila; Yuliati, Lilis; Erlangga, Okyviandi Putra (JIES : Journal of Islamic Economics Studies, 2026)
This study aims to analyze the implementation of musyarakah contracts in the mertelu farming system at the Sido Makmur Farmer Group in Sabrang Village, as well as to evaluate the level of farmer welfare through the perspective of maqashid syariah. This study uses a qualitative case study approach, collecting data through observation, documentation, and in-depth interviews with landowners and cultivators. The results show that the mertelu practice (1:3 profit sharing) has substantially fulfilled the principles of muzaraah and mukhabarah contracts. From the perspective of maqashid syariah, the welfare of tenant farmers has been partially achieved, especially in terms of religious preservation (hifz ad-din) and property preservation (hifz al-mal). However, this welfare is still vulnerable in terms of preserving life (hifz an-nafs) and the sustainability of wealth due to dependence on verbal agreements, the absence of written risk mitigation for crop failure, and market price fluctuations. This study concludes that although the mertelu system provides benefits for farmers, formal contracts are needed to ensure legal certainty and more stable economic protection for tenant farmers in the future.